Encounters of performance philosophy - Cull, Laura; Lagaay, Alice (New York Palgrave Macmillan, 2014)
Encounters in Performance Philosophy is a collection of 14 essays by international scholars and practitioners from across the disciplines of Philosophy, Literature and Theatre and Performance Studies, addressing the nature of the relationship between philosophy and performance. The essays cover a wide range of concerns common to performance and philosophy including: the body, language, performativity, mimesis and tragedy.The essays introduce and demonstrate the vitality of the emerging field of Performance Philosophy today, but they also provide thorough analyses of the rich history of thinking and practice that this new field inherits. Chapters engage with the work of theatrical philosophers and philosophical theatre makers from the ancient, modern and contemporary periods. Topics addressed include the work of Socrates, Plato, Nietzsche, Deleuze, J.L. Austin, Merleau-Ponty, Heidegger and Lacoue-Labarthe; explored in relation to practices from Greek tragedy and Shakespeare, music and actor training, to experimental theatre and site-specific performance.